The relationship between occupational stressors and insomnia in hospital nurses: The mediating role of psychological capital - Wang, Mei-Fang; Shao, Pei; Wu, Chao; Zhang, Lin-yuan; Zhang, Lan-fang; Liang, Juan; Du, Juan (Frontiers in Psychology, 2023)
Background：Nurses play an important role in medical and health services but insomnia among those in this profession is widespread. Insomnia not only damages the physical and mental health of nurses, but also reduces the efficiency of their work and the quality of care, ultimately impacting on patient care. Therefore, it is necessary to elucidate the factors that lead to insomnia and explore measures to reduce the impact these factors have on nurses. Objective: This study aimed to investigate the factors influencing insomnia in nurses and explored the mediating effect of psychological capital on occupational stressors, which was determined based on Karasek’s demand-control-support model, and insomnia among Chinese nurses. Methods: The Strengthening the Reporting of Observational Studies in Epidemiology statement was referred to conduct the study. Questionnaires were used to obtain data on demographic variables, psychological capital, occupational stressors, and insomnia. Descriptive analysis, independent-samples T-test, one-way analysis of variance, stratified regression analysis, Pearson correlation analyses, ordinary least-squares regression and the bootstrap method were used to analyze data. Results: The study findings revealed that work settings (department (F = 3.08, p = .006), working hours per week (t = −2.03, p = .043) and shift work(t = 3.66, p  .001)), decision latitude (r = −.25, p < .001), psychological job demand (r = .15, p < .001), social support (r = −.31, p < .001), and psychological capital (r = −.40, p < .001) were differentially associated with insomnia experiences. This empirical study showed that psychological capital has significant mediation effects on the relationship between occupational stressors and insomnia. Conclusions: The work department, weekly working hours,decision latitude, job demands, social support were the main influencing factors of insomnia. Psychological capital not only had a direct effect on both occupational stress dimensions and insomnia, but also played mediating roles in relationship between occupational stress dimensions and insomnia.